2021
DOI: 10.1080/10615806.2021.1876226
|View full text |Cite
|
Sign up to set email alerts
|

The centrality of a loss-event: Patterns, correlates, and predictive value

Abstract: Background and objectives: Evidence shows that the centrality of a lossevent maintains emotional distress following loss. Aims of the current study were to examine (i) if subgroups of bereaved people can be distinguished based on their endorsement of different manifestations of loss-centrality, (ii) if subgroup membership was associated with socio-demographic and loss-related variables, and (iii) the linkage of subgroup membership with symptom-levels of prolonged grief (PG), posttraumatic stress (PTS), and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These results confirm our hypothesis and replicate the findings with the abbreviated Dutch CES (Vermeulen et al, 2020). It also adds to the growing body of research questioning the direct relation between event centrality and depression (Janssen et al, 2015; Newby & Moulds, 2011), suggesting that event centrality is more typically related to PTSD, or, at least, related to specific traumatic experiences (e.g., grief; Boelen, 2021). Our results showed that individuals who reported a DSM-5 trauma A-criterion event had higher levels of event centrality than individuals without a history of trauma, although only a small to medium effect size was found.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm our hypothesis and replicate the findings with the abbreviated Dutch CES (Vermeulen et al, 2020). It also adds to the growing body of research questioning the direct relation between event centrality and depression (Janssen et al, 2015; Newby & Moulds, 2011), suggesting that event centrality is more typically related to PTSD, or, at least, related to specific traumatic experiences (e.g., grief; Boelen, 2021). Our results showed that individuals who reported a DSM-5 trauma A-criterion event had higher levels of event centrality than individuals without a history of trauma, although only a small to medium effect size was found.…”
Section: Discussionmentioning
confidence: 99%
“…Greater centrality of traumatic memories has been found to positively correlate with symptoms of post-traumatic stress disorder (PTSD) (Berntsen and Rubin, 2006: 228; see also Boals and Ruggero, 2016; Gehrt et al, 2018). The concept of event centrality has been explored and discussed in a wide range of contexts (see, for example, Boelen, 2021; Cook et al, 2021; Glad et al, 2020; Mordeno et al, 2018). To our knowledge, this interdisciplinary and exploratory article is the first to apply the CES to victims-/survivors 1 of conflict-related sexual violence (CRSV).…”
Section: Introductionmentioning
confidence: 99%